Has the Regulation of Non-GAAP Disclosures Influenced Managers' Use of Aggressive Earnings Exclusions?. (April 2017) - Black, Ervin L.; Christensen, Theodore E.; Kiosse, Paraskevi Vicky; Steffen, Thomas D.
The frequency of non-GAAP (or "pro forma") reporting has continued to increase in the United States over the last decade, despite preliminary evidence that regulatory intervention led to a decline in non-GAAP disclosures. In particular, the Sarbanes–Oxley Act of 2002 (SOX) and Regulation G (2003) impose strict requirements related to the reporting of non-GAAP numbers. More recently, the Securities and Exchange Commission (SEC) has renewed its emphasis on non-GAAP reporting and declared it a "fraud risk factor." Given the SEC's renewed emphasis on non-GAAP disclosures, we explore the extent to which regulation has curbed potentially misleading disclosures by investigating two measures of aggressive non-GAAP reporting. Consistent with the intent of Congress and the SEC, we find some evidence that managers report adjusted earnings metrics more cautiously in the post-SOX regulatory environment. Specifically, the results suggest that firms reporting non-GAAP earnings in the post-SOX period are less likely to (a) exclude recurring items incremental to those excluded by analysts and (b) use non-GAAP exclusions to meet strategic earnings targets on a non-GAAP basis that they miss based on Institutional Brokers' Estimate System (I/B/E/S) actual earnings. However, we also find that some firms exclude specific recurring items aggressively. Overall, the results suggest that while regulation has generally reduced aggressive non-GAAP reporting, some firms continue to disclose non-GAAP earnings numbers that could be misleading in the post-SOX regulatory environment.